Social isolation in space: An investigation of LUNARK, the first human mission in an Arctic Moon analog habitat - Riva, Paolo; Rusconi, Patrice; Pancani, Luca; Chterev, Konstantin (Acta Astronautica, 2022)
Research to address the technical challenges of human missions into space is growing. Knowledge about the social-psychological aspects of individuals’ experiences of confinement within habitats in space missions or extreme environments is also rapidly expanding. Social isolation is among one of the best-known risk factors in these environments. This study focuses on the relationship between time spent in specific activities (e.g., talking about personal matters) and the social-psychological effects of social isolation and confinement as a part of the LUNARK project, which was aimed at building and testing the first Moon analog habitat. Two space architects took part in a 61-day mission in Northern Greenland to simulate human life conditions in the habitat as a prototype of a human settlement on the Moon. The two crew members independently filled out a time-based diary with self-report measures on their daily activities and negative emotions, feelings of loneliness, resignation, desire for social contact, and time perception. First, our results showed that, for either space architect, desire for social contact increased over time, whereas feelings of resignation did not. Moreover, the protective role of specific daily activities emerged. Talking about personal matters and leisure time were associated with a decrease in resignation, whereas talking about personal topics and physical exercising increased the desire for social contact. Finally, engaging in leisure activities increased the perceived speed of time. We discussed these results referring to research on the consequences of long-term social isolation in extreme human expeditions and social psychological models of social isolation.